Ultrastructural Characteristics of Rat Hepatic Oval Cells and Their Intercellular Contacts in the Model of Biliary Fibrosis: New Insights into Experimental Liver Fibrogenesis - Joanna Maria Lotowska; Maria Elzbieta Sobaniec-Lotowska; Dariusz Marek Lebensztejn; Urszula Daniluk; Piotr Sobaniec; Krzysztof Sendrowski; Jaroslaw Daniluk; Joanna Reszec; Wojciech Debek (Gastroenterology Research and Practice)
Purpose. Recently, it has been emphasized that hepatic progenitor/oval cells (HPCs) are significantly involved in liver fibrogenesis. We evaluated the multipotential population of HPCs by transmission electron microscope (TEM), including relations with adherent hepatic nonparenchymal cells (NPCs) in rats with biliary fibrosis induced by bile duct ligation (BDL). Methods. The study used 6-week-old Wistar Crl: WI(Han) rats after BDL for 1, 6, and 8 weeks. Results. Current ultrastructural analysis showed considerable proliferation of HPCs in experimental intensive biliary fibrosis. HPCs formed proliferating bile ductules and were scattered in periportal connective tissue. We distinguished 4 main types of HPCs: 0, I, II (bile duct-like cells; most common), and III (hepatocyte-like cells). We observed, very seldom presented in literature, cellular interactions between HPCs and adjacent NPCs, especially commonly found transitional hepatic stellate cells (T-HSCs) and Kupffer cells/macrophages. We showed the phenomenon of penetration of the basement membrane of proliferating bile ductules by cytoplasmic processes sent by T-HSCs and the formation of direct cell-cell contact with ductular epithelial cells related to HPCs. Conclusions. HPC proliferation induced by BDL evidently promotes portal fibrogenesis. Better understanding of the complex cellular interactions between HPCs and adjacent NPCs, especially T-HSCs, may help develop antifibrotic therapies in the future.